The Effect of Profitability, Company Size, and Independent Commissioners on Tax Management - Angelina Fandy Arman; Margareta Febe; Vianty Adella Santo (Universitas Pelita Harapan, 2025)
This study aims to analyze the effect of profitability, firm size, and independent commissioner on tax management in consumer cyclicals sector companies listed on the Indonesia Stock Exchange for the period 2021–2023. The research employs a quantitative approach using secondary data from financial statements. The sample consists of 25 companies selected through purposive sampling. Data analysis was conducted using multiple linear regression with SPSS version 25. The results of the study indicate that, simultaneously, the three variables influence tax management. Profitability has a negative effect on tax management, firm size has a positive effect on tax management, while independent commissioner has no significant effect on tax management. This study concludes that profitability and firm size are important factors that can influence a company’s tax management practices. Therefore, companies need to implement efficient and legal tax management strategies.